2017
DOI: 10.1080/15226514.2017.1284743
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of hydrocarbons from freshwater green microalgae (Botryococcus sp.) biomass after phycoremediation of domestic wastewater

Abstract: This study was undertaken to analyze the efficiency of Botryococcus sp. in the phycoremediation of domestic wastewater and to determine the variety of hydrocarbons derived from microalgal oil after phycoremediation. The study showed a significant (p < 0.05) reduction of pollutant loads of up to 93.9% chemical oxygen demand, 69.1% biochemical oxygen demand, 59.9% total nitrogen, 54.5% total organic carbon, and 36.8% phosphate. The average dry weight biomass produce was 0.1 g/L of wastewater. In addition, the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The results from OLA display a different scenario. In particular, with the control group, f/2 medium, there was a drastic reduction from 49.0 to 33.1 μg mL −1 for the concentration of OLA after 12 h. All the groups were aerated, and it has previously been reported that this could affect the removal of some pollutants in the growth medium [ 33 ]. The same trend occurred in all the groups, a drastic reduction in the first 12 h, with a more pronounced reduction in the group of immobilised cells, from 49.0 to 29.9 μg mL −1 , and in the free cells group, from 49.0 to 19.8 μg mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The results from OLA display a different scenario. In particular, with the control group, f/2 medium, there was a drastic reduction from 49.0 to 33.1 μg mL −1 for the concentration of OLA after 12 h. All the groups were aerated, and it has previously been reported that this could affect the removal of some pollutants in the growth medium [ 33 ]. The same trend occurred in all the groups, a drastic reduction in the first 12 h, with a more pronounced reduction in the group of immobilised cells, from 49.0 to 29.9 μg mL −1 , and in the free cells group, from 49.0 to 19.8 μg mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The growth of Botryococcus sp reached a half of the log phase at 8 or 9 days. Gani et al, (2017) reported that the middle of exponential phase of Botryococcus sp was 12 days. On the basis of these data, Botryococcus sp with a 9 day age was chosen for use in the operation of a simple ICAF system with a variety of electric currents and operating times.…”
Section: Population Reduction Of Isochrysis Galbanamentioning
confidence: 99%
“…Methanolic extracts of exopolysaccharides Antioxidant [40] Botryococcus braunii Linear alkadienes (C25, C27, C29, and C31), triene (C29) Phycoremediation [41] Chlorella sp.…”
Section: Arthrospira Platensismentioning
confidence: 99%